In vitro assessment of the probiotic properties of an industrial preparation containing Lacticaseibacillus paracasei in the context of athlete health - Brunelli, Laura; De Vitis, Valerio; Ferrari, Roberto; Minuzzo, Mario; Fiore, Walter; Jäger, Ralf; Taverniti, Valentina; Guglielmetti, Simone (Frontiers in Pharmacology, 2022)
Intense physical activity is often associated with undesirable physiological changes, including increased inflammation, transient immunodepression, increased susceptibility to infections, altered intestinal barrier integrity and increased oxidative stress. Several trials suggested that probiotics supplementation may have beneficial effects on sport-associated gastro-intestinal and immune disorders. Recently, in a placebo-controlled human trial, the AminoAlta™ probiotic formulation (AApf) was demonstrated to increase the absorption of amino acids from pea protein, suggesting that the administration of AApf could overcome the compositional limitations of plant proteins. In this study, human cell line models were used to assess in vitro the potential capacity of AApf to protect from the physiological damages that an intense physical activity may cause. The obtained results revealed that the bacteria in the AApf have the ability to adhere to differentiated Caco-2 epithelial cell layer. In addition, the AApf was shown to reduce the activation of NF-κB in Caco-2 cells under inflammatory stimulation. Notably, this anti-inflammatory activity was enhanced in the presence of partially hydrolyzed plant proteins. The AApf also triggered the expression of cytokines by the THP-1 macrophage model in a dose-dependent manner. In particular, the expression of cytokines IL-1β, IL-6, and TNF-α was higher than that of the regulatory cytokine IL-10, resembling a cytokine profile characteristic of M1 phenotype, which typically intervene in counteracting bacterial and viral infections. Finally, AApf was shown to reduce trans-epithelial permeability and increase superoxide dismutase activity in the Caco-2 cell model. In conclusion, this study suggests that the AApf may potentially provide a spectrum of benefits useful to dampen the gastro-intestinal and immune detrimental consequences of an intense physical activity.